1999
DOI: 10.1200/jco.1999.17.2.658
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan Versus Cyclophosphamide, Doxorubicin, and Vincristine for the Treatment of Recurrent Small-Cell Lung Cancer

Abstract: Topotecan was at least as effective as CAV in the treatment of patients with recurrent SCLC and resulted in improved control of several symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
525
5
21

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 843 publications
(563 citation statements)
references
References 21 publications
12
525
5
21
Order By: Relevance
“…In addition to the randomized trial comparing oral topotecan with BSC mentioned above, 2 phase 3 trials for recurrent SCLC have been reported to date. 14,15 A trial comparing intravenous topotecan with the combination of cyclophosphamide, doxorubicin, and vincristine demonstrated comparable response rates and survival; however, intravenous topotecan yielded greater symptomatic improvement for 4 of the 8 symptoms evaluated. 14 In the other trial, comparing oral topotecan with intravenous topotecan, no survival difference was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the randomized trial comparing oral topotecan with BSC mentioned above, 2 phase 3 trials for recurrent SCLC have been reported to date. 14,15 A trial comparing intravenous topotecan with the combination of cyclophosphamide, doxorubicin, and vincristine demonstrated comparable response rates and survival; however, intravenous topotecan yielded greater symptomatic improvement for 4 of the 8 symptoms evaluated. 14 In the other trial, comparing oral topotecan with intravenous topotecan, no survival difference was observed.…”
Section: Discussionmentioning
confidence: 99%
“…8 The next step was a randomized comparison of topotecan and the combination of cyclophosphamide, doxorubicin and vincristine (CAV) in patients who had relapsed more than 3 months after completion of first line therapy. 9 Topotecan proved to be as effective as CAV in terms of response, but was more effective in controlling a number of disease-related symptoms. In the next randomized trial, topotecan was tested after completion of first-line therapy in patients with extensive stage SCLC.…”
Section: First or Second Line?mentioning
confidence: 98%
“…In SCLC, topotecan has comparable response rates and survival to CAV (cyclophosphamide 1,000 mg/m 2 , doxorubicin 45 mg/m 2 , and vincristine 2 mg, D1, every 21 days) with less toxicity. 99 Oral topotecan 2.3 mg/m 2 /day for 5 days, when compared to intravenous 1.5 mg/m 2 /day for 5 days every 21 days, resulted in comparable median survival at 2 years, therefore constituting an alternative to the intravenous formulation. 100 …”
Section: Recommendationmentioning
confidence: 99%